(untitled) (American Journal of Islam and Society, 2004)
A host of recent events – well known to all and not in need of rehearsal here – have had, among a variety of other consequences, the unexpected effect of focusing the world’s attention on the diversity of Muslims and the Islamic tradition. The constant talk of “Sunni triangles,” “Shi`ite clerics,” and “Wahhabi radicals,” however, raises important questions about what precisely divides the Muslim community along these lines. For Ayoub, the roots of this sectarianism can be found, at least in part, in the crucial historical time period known as the Rashidite (or “Rightly Guided”) caliphate. It is the “political and socio-religious crisis” (p. 4) of this era (stretching from the death of the Prophet until `Ali’s assassination) and its implications for subsequent generations, that form the subject matter of this book. Ayoub envisions his work as filling a void found in most general introductions to Islam, which for all their other merits, often fail to provide a clear account of this formative period of Islamic history. As for those who have ventured to write in the area, Ayoub considers the works of both Muslim and western scholars to be fraught with the political and theological biases of their authors. His desire to avoid this pitfall motivates him to adopt the novel approach of letting the “primary sources of Muslim thought and history” (p. 4) speak for themselves, a tack not unlike the one he uses in his important contribution to tafsir studies: The Qur’an and Its Interpreters. Using this methodology, Ayoub seeks to construct and present a balanced account of the major historical events of the Rashidite era in an effort to explore the interaction between considerations of religion and politics in early Islamic understandings of the nature of authority. His analysis of the various claims to the caliphate advanced by Abu Bakr, `Umar, `Uthman, and `Ali, as well as by less successful contenders, is aimed at supporting his central assertion that because “the Prophet died without leaving a clear political system” (p. 22), the Companions did not agree – indeed they vehemently disagreed – on answers to questions of political authority: ...